Assessing the nuances of counterterrorism programs: a country-level investigation of targeted killings - Carson, Jennifer Varriale (Crime & delinquency, 2019)
Although there has been research assessing the effectiveness of targeted killings in a variety of contexts, there remains important gaps in the literature. This study addresses these gaps by evaluating previously established nuanced effects together in one analysis, while at the same time incorporating vital country-level controls. This investigation utilizes two types of analytic strategies, ZINB and series hazard models, with multiple independent and dependent variables. Overall, this study fails to find clear evidence that targeted killings are correlated with terrorism outcomes in the three countries in which they are most commonly used: Pakistan, Yemen, and Somalia.